2020
DOI: 10.1002/bit.27432
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐scale scaffolds for the Chinese hamster reference genome assembly to facilitate the study of the CHO epigenome

Abstract: The Chinese hamster genome serves as a reference genome for the study of Chinese hamster ovary (CHO) cells, the preferred host system for biopharmaceutical production.Recent re-sequencing of the Chinese hamster genome resulted in the RefSeq PICR metaassembly, a set of highly accurate scaffolds that filled over 95% of the gaps in previous assembly versions. However, these scaffolds did not reach chromosome-scale due to the absence of long-range scaffolding information during the meta-assembly process. Here,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…further exemplifies to the CHO community the power of Hi-C mediated genome scaffolding, are consistent with those published for the recent PICRH Chinese hamster assembly(Hilliard et al, 2020) and in line with what would be expected given the haploid chromosome number of the CHOK1SV 10E9 cell line. The ≈10% of sequence not included within the final chromosome-scale assembly remain pertinent for continued improvements to the assembly.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…further exemplifies to the CHO community the power of Hi-C mediated genome scaffolding, are consistent with those published for the recent PICRH Chinese hamster assembly(Hilliard et al, 2020) and in line with what would be expected given the haploid chromosome number of the CHOK1SV 10E9 cell line. The ≈10% of sequence not included within the final chromosome-scale assembly remain pertinent for continued improvements to the assembly.…”
supporting
confidence: 87%
“…Similar levels of alignment consistency were also witnessed in comparison to the Chinese Hamster PICR reference assembly(Rupp et al, 2018; data not shown). Finally, in terms of both the overall cis/trans ratio and the distribution of close cis and far cisinteractions, data aligned to the CHOK1SV 10E9 LACHESIS assembly was comparable to high-quality human and mouse Hi-C datasets(Nagano et al, 2015;Figure 2c).The integration of data, such as long-read PacBio sequencing, along with a comparative analysis to the PICRH Chinese hamster assembly(Hilliard et al, 2020), should help refine the CHOK1SV 10E9 cell line assembly further. Importantly, however, our assembly can be used to mediate the hierarchical identification of higher order 3D chromatin structures within the CHOK1SV 10E9 cell line and could be used as a framework to aid all facets of CHO cell line genomics research where a chromosome-scale assembly is of paramount importance.…”
mentioning
confidence: 87%
“…FDR less than 0.05 and absolute logFC greater than one were used as cutoffs to classify genes as differentially expressed. After differential expression analysis, gene coordinates in the PICR assembly were converted to chromosomal coordinates using annotations lifted over from PICR to the PICRH assembly as described previously (Hilliard et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Reproducibility and whole chromosome similarity between the Hi-C interaction frequency matrices of host and producer cell lines was assessed by calculating the stratum-adjusted correlation coefficients (SCC) for Chinese hamster chromosomes 1 through 10 and X at 100-kb resolution using HiCRep (Yang et al, 2017). SCC was also used to score host and producer similarity to the Chinese hamster interaction frequency matrix described previously (Hilliard et al, 2020) at 1-Mb resolution. SCC was calculated for interaction frequency matrices that were generated using a version of the PICRH genome assembly with a fully intact chromosome 1 (concatemer of chr1_0 and chr1_1).…”
Section: Hi-c Reproducibility and Whole Chromosome Similarity Scoringmentioning
confidence: 99%
“…Steady improvements in cell line development, media formulation, and bioprocessing now enable production yields exceeding 10 g/L from a fed-batch culture. Emerging resources, including the CHO and hamster genome sequence [3][4][5][6][7][8] and genome editing tools [9][10][11][12][13][14] now allow researchers to rely less on largely empirical, "trial-and-error" approaches to CHO cell line development, and move towards a more rational engineering approach, in pursuit of novel CHO lines with tailored, superior attributes [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%